Gold nanorods (GNRs): a golden nano compass to navigate breast cancer by multimodal imaging approaches - Varma, Sanjana; Bamb, Aagam Lalit; Haldar, Niladri; Gajbhiye, Virendra; Amalnerkar, Dinesh; Chaudhari, Bhushan Pradosh (Journal of Biomedical Materials Research Part B-Applied Biomaterials, 2025)
The ongoing rise in the incidences of breast cancer cases has concerned medical and scientific personnel around the world. Adequate treatment of cancer predominantly relies on the pertinent diagnosis of the type of cancer as well as other molecular and cellular details at the initial stage only. Surprisingly, up till now, there is no single, self-reliant imaging modality that helps to systematically find out the anatomical and functional events taking place inside the body. This resulted in the advent of the multimodal imaging concept, which encompasses the integration of complementary imaging modalities by designing multimodal imaging probes. Gold nanorods (GNRs) are extremely popular and effective nanoparticles for multimodal bioimaging due to their unique properties. Researchers have designed varieties of stable and biocompatible GNR-based probes for targeted and nontargeted multimodal imaging of breast cancer. However, there is a lack of investigations on the in vivo fate and the toxicity of GNRs. Thus, their preclinical to clinical translation can be attained by comprehensively determining the in vivo fate and toxicity of GNRs. The review provides details about the GNRs-based nanoprobes fabricated so far for breast cancer imaging, which, by consequent studies, can be taken up to clinical usage.
Keywords: Breast cancer; Gold nanorods; imaging probes; Multimodal Imaging

An integrated paradigm to understand the antibacterial and antifungal potential of bimetallic core-shell platinum silver (Pt@Ag) nanoparticles: A one health approach - Bamb, Aagam Lalit; Varma, Sanjana; Gade, Tejas Subhash; Palaskar, Shahaji; Vamkudoth, Koteswara Rao; Vyawahare, Niraj; Chaudhari, Pallavi M.; Chaudhari, Bhushan P. (Microbial Pathogenesis, 2025)
The concurrent occurrence of various microbial infections escalates the need to develop new treatments that can tackle multiple microbes and improve clinical outcomes. This study reports the synthesis and comprehensive evaluation of core-shell platinum-silver nanoparticles (Pt@AgNPs) designed to elucidate the antimicrobial effects while ensuring biocompatibility. The synthesis protocol was meticulously optimized to investigate the impact of precursor concentrations and reagent conditions. High-end characterization confirmed the formation of a welldefined core-shell structure with spherical morphology, crystalline nature, a face-centred cubic (FCC) lattice, high monodispersity, and stability, with a mean size of 20.344 +/- 4.492 nm. The antimicrobial potential of Pt@AgNPs was validated through a minimum inhibitory concentration (MIC) assay, revealing potent activity with MIC values of 15.6 mu g/mL for Pseudomonas aeruginosa and Staphylococcus aureus and 3.9 mu g/mL for Escherichia coli. Antibiofilm assay demonstrated significant inhibition of biofilm formation by P. aeruginosa at concentrations as low as 3.9 mu g/ml. The nanoparticles also exhibited notable antifungal activity, as indicated by an inhibition of 65.19 % for Aspergillus niger and 61.82 % for Fusarium verticillioides. Furthermore, hemocompatibility was noticed with the hemolysis assay, and the antioxidant properties of nanoparticles, assessed through the 2,2-diphenyl-1-picrylhydrazyl (DPPH) assay, underscored their potential to mitigate oxidative stress. This integrative study positions Pt@AgNPs as a promising platform for combating the occurrence of co-infections. The core-shell nanoparticle serves as a versatile tool in antimicrobial defence, exhibiting antibacterial, antifungal, antibiofilm, and antioxidant activity. Thus, it highlights their commercial translational potential as a next-generation antimicrobial intervention.
Keywords: Antibacterial; antibiofilm; antifungal; Antioxidant; Co-infections; Pt@Ag nanoparticles

Understanding the antimicrobial and antioxidant potential of bioinspired platinum nanoparticles synthesized using ocimum tenuiflorum - Varma, Sanjana; Bamb, Aagam Lalit; Tambe, Sayali A.; Burade, Dimpal K.; Jagdale, Swati; Pande, Bharat; Vamkudoth, Koteswara Rao; Chaudhari, Bhushan P. (BioNanoScience, 2025)
The emergence of infectious diseases has highlighted the need for novel and effective antimicrobial agents. Platinum nanoparticles (PtNPs) could act as a potent antimicrobial agent due to their unique physicochemical properties. However, the chemical or physical synthesis methods of PtNPs have drawbacks, like irregular shape and use of toxic chemicals. These drawbacks can be effectively overcome by using the biological method synthesis. Thus, this study presents the green synthesis of platinum nanoparticles (PtNPs) using Ocimum tenuiflorum leaf extract as a bio-reductant. The study also comprehensively encompasses the role of multiple process parameters for the green synthesis of PtNPs. The high-resolution transmission electron microscopy (HR-TEM) revealed spherical PtNPs with an average size of 2.36 ± 0.5 nm that exhibits excellent stability (zeta potential, −45.67 ± 2.57 mV). Phytochemical analysis of aqueous O. tenuiflorum leaf extract was performed to assess the bioactive compounds like saponins, phenols, and tannins, reducing sugars and flavonoids. The PtNPs demonstrated significant antioxidant activity of 86.9 ± 0.12% at 10 µg/mL. Further, the biosynthesized PtNPs showed efficient antimicrobial activity with a minimum inhibitory concentration (MIC) of 6.25 µg/mL against Escherichia coli and 1.5 µg/mL against Staphylococcus aureus. These findings highlight the therapeutic potential of eco-friendly PtNPs for pharmaceutical and biotechnological applications.